Der Zuschauerraum des Theaters von Ephesos Baubefund und architekturhistorische Analyse - Styhler-Aydin, Gudrun (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The publication presents the results of recent building archaeology in the auditorium of the theater, conducted in the years 2003-2011. Starting with an introductory presentation on the history of research and the current state of preservation, the main section deals in detail with the construction phases of the auditorium from Hellenism to the Byzantine period. On the basis of drawings, maps and photos, nearly 800 years of architectural history are explained vividly and comprehensibly and discussed by comparison of apt buildings. Contributions to sculptures in the theatre and to the investigation of ancient mortar complement the findings.